Figure 7 from: Philippov DA, Ivicheva KN, Makarenkova NN, Filonenko IV, Komarova AS (2022) Biodiversity of macrophyte communities and associated aquatic organisms in lakes of the Vologda Region (north-western Russia). Biodiversity Data Journal 10: e77626. https://doi.org/10.3897/BDJ.10.e77626 - Philippov, Dmitriy; Ivicheva, Ksenya; Makarenkova, Nadezhda; Filonenko, Igor; Komarova, Aleksandra (Zenodo, 2022)
Figure 7 An intra-mire lake, Korovye Lake (Vologda Region, Russia). Photo by Dmitriy A. Philippov (2019).